Provocation to Dialog in a Third Space: Helping Teachers Walk Toward Equity Pedagogy - Ratnam, Tara (Frontiers in Education, 2020)
This study examines the conceptual basis of how teachers learn, including, importantly, how they learn to relate to social concerns of equity in their teaching, and makes this understanding experientially accessible using a live case of the “practical” (Schwab, 1969). The conceptual understanding emerges from questioning the assumptions behind the valorization in teacher education of “theory” over “practice” that has led to the “theory into practice”/“input–output” model of teacher education. An examination of the constraints posed by this monolithic model of teacher education to teacher learning, development, and change has provided the impetus to work toward a more pluralistic view of knowledge and the new understanding of the nature of teacher learning which ensues. This alternative formation, which is informed by insights from the sociocultural perspectives of Lev Vygotsky and Mikhail Bakhtin among others, has helped in constructing a view of teacher learning as taking shape in authentic social interaction in a “third space” through hybridization of diverse voices. Most importantly, the paper considers its implications for teacher education by abstracting from experience the nature of mediation that facilitates hybridization.